Очистные механизированные комплексы ОКП 70 - Портяненко В. И. Валерий Иванович; Мозжухин А. В. Альберт Васильевич; Щербаков Н. И. Николай Иванович; Кривопуск В. К.; Ермаков Ф. А. (Москва, Недра, 1984)
Авт. указаны на обороте тит. л.